PENGARUH TRANSPARANSI, AKUNTABILITAS DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN ALOKASI DANA DESA DI DESA SIDOHARJO KECAMATAN SIDOHARJO KABUPATEN SRAGEN - Firdaus, Anita; Suharno, Suharno; Sunarti, Sunarti (Universitas Slamet Riyadi, 2019)
The study aims to examine the influence of transparency, accountability and society participation management of village fund allocation. The study used survey method with questionnairs as its instrument. The population of this study are the rural society and officials village Sidoharjo sub-district Sidoharjo in the district of Sragen. Based on purposive sampling , the number of samples obtained is 80 people. The type in this study is a quantitative study with a view to found the truth contained in this study, which is using multiple linear regression test and tested the validity and reliability the quality of the questionnairs with SPSS 21sofware application. The result of this study found that transparency, accountability and society participation have a significant positive effect management of village fund allocation. This study is expected to provide input for the rural goverment to synergize to improve transparency, accountability and society participation in management og village fund allocation.